Hegemonics constraints : the implications of 11 September for American power, by Evelyn Koh ; Terrorist use of weapons of mass destruction : how serious is the threat?, by Andrew O’Neil, - Cave Schnöhr, Rose (Estudios Internacionales, 2003)
Reseña de dos artículos publicados en: Australian Journal of International Affairs, Vol. 57, Nº 1, April 2003, p. 77-112